COMPARISON OF OBJECTIVE STRUCTURED CLINICAL EXAMINATION WITH TRADITIONAL PRACTICAL EXAMINATION IN ASSESSMENT OF NURSING STUDENTS’ CLINICAL COMPETENCIES IN SOUTHWESTERN NIGERIA (2017)
Clinical examination is crucial to assess competencies of nursing students in the delivery of quality nursing care. Globally, Traditional Practical Examination (TPE) and Objective Structured Clinical Examination (OSCE) are the methods of clinical assessments in Nursing. The Nursing and Midwifery Council of Nigeria (NMCN) had always used TPE for clinical examinations. The NMCN adopted OSCE for midwifery two decades ago while the examination in general nursing remains TPE. There is dearth of information on the effectiveness of OSCE and TPE in assessing students in general nursing. The goal of this study was to compare the effectiveness of OSCE and TPE in the assessment of clinical competencies of nursing students in Southwestern Nigeria. The study utilised quasi-experimental design among nursing students. Using a ballot system, two out of the sixteen hospital-based and two out of the five university-based nursing programmes were selected. The four schools participated in OSCE and TPE. The two programmes have similar curricula for nursing clinical procedures. Out of the 186 nursing students selected, 100 were second year hospital-based (51 students in Wesley Guild School of Nursing, Ilesa and 49 students in School of Nursing, Akure) while 86 were 300 level university-based (36 students in the Department of Nursing, University of Ibadan and 50 students in the Department of Nursing, Ladoke Akintola University of Technology, Osogbo). Data were obtained using adapted and validated instruments: Traditional Practical Examination Instrument (TPEI), Objective Structured Clinical Examination Instruments (OSCEIs) and Students’ Demographic and Perception Questionnaires (SDPQ). Pre-test was administered to the students to obtain the baseline data after which clinical teaching of selected nursing procedures were taught to all students for four weeks. The TPE (post-test I) was conducted at fifth week while OSCE (post-test II) was conducted at sixth week. The means of the performance scores in OSCE and TPE were computed while competency data were obtained by grouping performance scores into two levels of competencies: fairly competent (50.0%-59.9%) and very competent (60.0% and above). The SDPQ was used to collect data on students’ preference and perception of the two examination formats. Data were analysed using descriptive statistics, Students t-test, Chi-square test and ANOVA at α0.05. Age of respondents was 21.5±3.8 years. At baseline, the mean of students’ performance score was 53.3±3.7. There was a significant difference between the mean scores obtained at baseline and the two practical examination formats: pre-test 53.3±3.7, OSCE(post-test II) 64.6±5.2, TPE (post-test I) 59.3±2.9. More respondents were very competent in OSCE (80.1%) compared to TPE (45.7%). Perception of Objective Structured Clinical Examination and Traditional Practical Examination revealed: consumed less time (53.0% versus 48.0%); more objective (52.1% versus 47.9%); assessed wider range of learned materials (54.4% versus 45.6%); less destabilizing during practical sessions (53.5% versus 46.5%) less stressful (56.1% versus 44.0%). Lastly, 56.8% of respondents preferred OSCE while 43.2% preferred TPE. Objective Structured Clinical Examination was more effective in assessing competency of nursing students.